Ethnic Boundaries in Contemporary Rwanda: Fixity, Flexibility and Their Limits - Eramian, Laura (Anthropologica, 2015)
This article investigates how ethnic boundaries operate at the level of everyday practice in post-genocide Rwanda. Using situational analysis of two ethnographic accounts, I argue that Rwandans experience ethnicity as both descent-based (fixed) and social-relational (flexible), the convergence of which finds expression in everyday forms of moral agency. An account of the historical emergence of Tutsi and Hutu ethnic stereotypes develops the idea that, in everyday life, there is no single criterion that Rwandans can use to conclusively resolve how they belong ethnically. Thus, the question of how and when ethnicity matters in the posUgenocide period remains uncomfortably open.